FAKTOR-FAKTOR MOTIVASI YANG MEMPENGARUHI MAHASISWA TERHADAP MINAT BERWIRAUSAHA - Nadya Monica Herdiani; Rahmat Hidayat (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
This study aims to determine the motivation factors to influence interest in entrepreneurship. Respondents of this research is a student of Batam State Polytechnic from the Department of engineering and non-engineering. This study using multiple linear regression analysis, where the analysis tool is used to know the extent of the influence of risk tolerance (X1), work freedom (X2), and self-efficacy (X3) to student interest in entrepreneurship (Y). The results of the partial test showed that risk tolerance and self-efficacy had a positive and significant effect, however work freedom do not affect significantly the interest in entrepreneurship. While the result of the simultaneous test indicated that all independent variable had a positive and significant effect on students’ interest in entrepreneurship.